Analisis Sejarah Ekonomi Terhadap Aliran Institusional - Anisa Sanas Nalamjra; Sasmi Ebigael Sinaga; Nur Aini Simbolon; Bonaraja Purba (Moneter : Jurnal Ekonomi dan Keuangan, 2024)
Institutional Economics is a school of thought in economics which contains the view that economic behavior, where a person or party is greatly influenced by certain institutions. In this case, institutions themselves have a fairly broad meaning and can be briefly defined as the "rules of the game" in a community group, both formal and informal, which are deliberately designed to limit or regulate relationships between people within that community group. Formal institutions can be in the form of rules, regulations, statutory law and others; while informal institutions can be conventions, trends, culture, and so on. Thus, institutions here are not the same as organizations. The Institutional School initially emerged as a refutation of the neo-classical economic view or school which states that a person's economic behavior is solely based on each individual's desire to maximize profits (maximizing profit behavior). The term "institutional economics" was first introduced by Walton Hamilton in 1919.